Bolívar y la constitución del discurso nacionalista en Venezuela - Luís J. González Oquendo (Les Cahiers ALHIM)
The central objective of this paper is analyze the patriotic speech associated to Simon Bolívar –Venezuelan General of early part of XIX Century that was the principal political and military leader of independents process of his country- like as key element in the constitution of nationalist discourse in Venezuela. For a better argumentative construction, we are going to divide the text in three sections. First, «Bolivar and Bolivarian tradition in Venezuela» consider how has been constructed the Venezuelan national identity throughout the image of Bolivar : it’s the historical position of processes, analyzed in long term. Therefore, «Bolivar like as reference of Nation according to Bolivarian Revolution», we are going to consider the production of nationalist discourse in a more restricted and contemporary temporal horizon, that is to say the political processes after 1992, constituted like government since 1999. Finally, trying to answer the question «Can be criticized the Bolivarian Reason?», We are going to articulate the elements that have to be consider to understand how people consider that position like a real natural order of things. In this way, We are trying to analyzed the position occupied by Bolivar in the processes of identitive construction in Venezuela.